PREVALENCE AND RISK FACTORS FOR INCISIONAL HERNIA FOLLOWING CESAREAN SECTION: A CROSS-SECTIONAL STUDY. - Sweta Rani; Anupam Ranjan; Girija Kumari (Student's Journal of Health Research Africa, 2024)
Background Cesarean section (C-section) is a prevalent surgical procedure globally, essential for managing complicated deliveries. However, it carries risks, including the development of incisional hernias, which can significantly impact maternal health and healthcare costs. This study investigated the prevalence and risk factors associated with incisional hernia following cesarean sections. Methods A cross-sectional observational study was conducted. Eighty-six women who underwent C-sections were included. Data on demographics, medical history, surgical details, and postoperative outcomes were collected through structured questionnaires and medical record reviews. Participants were followed up at 6 weeks, 3-, 6-, and 12 months post-surgery for physical examinations. Statistical analysis was accomplished. Results The average age was 29.4 years (± 5.6) and BMI was 26.7 kg/m² (± 4.1). Most participants (62.8%) were middle-class, and 18.6% smoked. The prevalence of incisional hernia was found to be 14.0%. Significant risk factors included higher BMI (OR: 1.15, p=0.035), hypertension (OR: 3.67, p=0.036), vertical incision type (OR: 4.82, p=0.037), postoperative wound infection (OR: 7.23, p=0.002), and low physical activity (OR: 3.21, p=0.046). These factors highlight the need for targeted interventions to reduce hernia incidence. Conclusion Incisional hernia is a common complication post-C-section, with significant risk factors identified as higher BMI, hypertension, vertical incisions, postoperative wound infections, and low physical activity. Recommendations To mitigate the risk of incisional hernia, it is recommended to manage patient weight and hypertension effectively, prefer Pfannenstiel incisions, ensure rigorous infection control, and promote appropriate postoperative physical activity.